Prognostic subclassifications of T1 cutaneous melanomas based on ulceration, tumour thickness and Clark's level of invasion: results of a population‐based study from the Swedish Melanoma Register. (18th January 2013) - Lyth, J.; Hansson, J.; Ingvar, C.; Månsson‐Brahme, E.; Naredi, P.; Stierner, U.; Wagenius, G.; Lindholm, C.; ,
Summary Background Survival and prognostic factors for thin melanomas have been studied relatively little in population‐based settings. This patient group accounts for the majority of melanomas diagnosed in western countries today, and better prognostic information is needed. Objectives The aim of this study was to use established prognostic factors such as ulceration, tumour thickness and Clark's level of invasion for risk stratification of T1 cutaneous melanoma. Methods From 1990 to 2008, the Swedish Melanoma Register included 97% of all melanomas diagnosed in Sweden. Altogether, 13 026 patients with T1 melanomas in clinical stage I were used for estimating melanoma‐specific 10‐ and 15‐year mortality rates. The Cox regression model was used for further survival analysis on 11 165 patients with complete data. Results Ulceration, tumour thickness and Clark's level of invasion all showed significant, independent, long‐term prognostic information. By combining these factors the patients could be subdivided into three risk groups: a low‐risk group (67·9% of T1 cases) with a 10‐year melanoma‐specific mortality rate of 1·5% (1·2–1·9%); an intermediate‐risk group (28·6% of T1 cases) with a 10‐year mortality rate of 6·1% (5·0–7·3%); and a high‐risk group (3·5% of T1 cases) with a 10‐year mortality rate of 15·6% (11·2–21·4%). The high‐ and intermediate‐risk groups accounted for 66% of melanoma deaths within T1. Conclusions Using a population‐based melanoma register, and combining ulceration, tumour thickness and Clark's level of invasion, three distinct prognostic subgroups were identified.